Information technology in mathematics education - Baskas, Antanas (Lietuvos matematikos rinkinys, 2004)
Information technology (IT), used both within classroom settings with well educated and motivated teachers and instructors and by individuals, has the potential to greatly increase the productivity and accessibility of education and training.